Editorial - Wit Pasierbek (Jesuit University Ignatianum in Krakow, 2017)
In his book entitled "Man's Problem", Martin Buber discusses the anthropological status of our times mentioning two factors, which have considerably influenced the comprehension, existence, identity and man's future; both of them exhibit traits of crisis. The first one can be identified in terms of sociology. Previous organic forms of direct contact between humans are collapsing rapidly. Man, through the continuously appearing variety of institutions, associations, parties, through globalisation, enters the world of anonymity, which excludes the possibility of direct relations in small groups, in communities that gave him the sense of safety, peace at heart. These communities, first of all, refer to the family, but also to the craft guild, the village and town commune, as well as other associations. In these, living tradition was cultivated and the history was recollected; therefore, they became the place where the sense of one's own identity could be felt.